The Tenderometer as a tool for evaluating beef tenderness - Tuma, H.J.; Allen, Dell M.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station, 2011)
Numerous instruments have been developed to objectively measure tenderness, an important eating characteristics of beef. The Kramer shear press and Warner-Bratzler shear show the best relationships to taste panel tenderness scores. However, shear values of raw muscle are poorly correlated with shear value of cooked meat. An instrument that could be used in the beef cooler an raw carcass muscle to predict tenderness of cooked meat would be valuable.
Keywords: Beef; Tenderness; Carcass value